Phenol removal from aqueous solutions by using H-mordenite and platinum supported H-mordenite - Hasanen, Jehan Abd Elrazek; Elhafez, Dalia Radwan Abd; Rashad, Ahmed Mohamed; Elazab, Waleed; Fathy, Ahmed Hussein (European Journal of Chemistry, 2015)
H-Mordenite and platinum supported H-mordenite were prepared and tested to remove phenol from aqueous solutions. The supported mordenite was prepared using wet impregnation method. The physicochemical properties of these prepared samples were characterized by several techniques such as SEM, HR-TEM, X-ray diffraction and N2 adsorption. The effects of temperature, pH, phenol concentration, catalyst amount and UV at 254 nm were studied to obtain the optimum conditions at which best removal occurs. It was seen that the removal using H-mordenite is close to the supported H-mordenite.